The Effectiveness of E-Learning System with Design Features as Mediating Variable - Grace T. Pontoh; Indriyanti Linting; Syamsuddin Syamsuddin (Journal of International Conference Proceedings (JICP), 2021)
The research aimed to examine the effect of technology acceptance, learning strategies, and cognitive assessment on the effectiveness of e-learning system with design features as mediating variable. Technology acceptance is explained by perceived usefulness (PU) and perceived ease of use (PEOU). The learning strategy is explained by deep learning and surface learning Cognitive assessment is explained by challenges and threats. The research was conducted at Hasanuddin University with total number of respondents are 295 (two hundred ninety-five) students in the accounting department. The data were processed using Structural Equation Modeling (SEM). The test result showed that through design features, PU, PEOU, deep learning had a positive effect on the effectiveness of e-learning system. Meanwhile, surface learning had a negative effect on the effectiveness of e-learning system. In addition, the result of this research indicated that challenges had no positive effect on the effectiveness of e-learning system and threats had no negative effect on the effectiveness of e-learning system. These results indicated that users will experience the benefits and convenience of e-learning system supported by a platform that has good design features. In addition, users will prefer to learn with deep learning approach so that they can improve learning effectiveness.